Toxicity and Efficacy Evaluation of Soluble Recombinant Ricin Vaccine - Hyeongseok Yun; Hae Eun Joe; Dong Hyun Song; Young-Jo Song; Sunghyun Hong; Chang-Hwan Kim; Na Young Kim; Gyeung Haeng Hur; Chi Ho Yu (Vaccines, 2024)
Background: Ricin, a toxin extracted from the seeds of Ricinus communis, is classified as a ribosome-inactivating protein. The A-subunit of ricin shows RNA N-glycosidase activity that cleaves ribosomal RNA (rRNA) and exhibits toxicity by inhibiting protein synthesis and inducing vascular leak syndrome. Methods: In this study, we created a truncated version of the previously developed R51 ricin vaccine (RTA 1-194 D75C Y80C) through in silico analysis. Results: The resulting R51-3 vaccine showed a more-than-six-fold increase in soluble protein expression when compared to R51, with over 85% solubility. In a pilot toxicity test, no toxicity was observed in hematological and biochemical parameters in BALB/c mice and New Zealand white rabbits following five repeated administrations of R51-3. Furthermore, R51-3 successfully protected mice and rabbits from a 20 × LD50 ricin challenge after three intramuscular injections spaced 2 weeks apart. Similarly, monkeys that received three injections of R51-3 survived a 60 µg/kg ricin challenge. Conclusions: These findings support R51-3 as a promising candidate antigen for ricin vaccine development.